A piezoelectric inchworm actuator of linear type using symmetrical lever amplification. (December 2015) - Ma, Li; Xiao, Jintao; Zhou, Shasha; Sun, Lining
Piezoelectric inchworm actuators have a wide application in the field of nano-positioning and ultra-precision detecting instruments. Ultra-precision positioning equipments are urgently needed in the field of precision optics. A new piezoelectric linear actuator, based on inchworm motion principle, with a symmetry lever displacement amplification mechanism has been designed in this article. The whole structure adopts uniaxial-type double-notch right circular flexible hinge as its main hinges, which offers the driving part a larger displacement and makes clamping part have enough clamping force at the same time. High-precision cross roller guide ways are utilized to improve the positioning accuracy of the actuator. Both theoretical analysis and finite element analysis of clamping mechanism and driving mechanism have been carried out. An experimental test platform has been built, and a controlling program of the actuator is compiled by LabVIEW. The experimental results show that the working stroke of the actuator is ± 25 mm, resolution is 60 nm, the clamping force is 17 N, and the bearing capacity is 11 N; the actuator has a highest speed of 1.259 mm/s at the driving voltage 150 V.